2008
DOI: 10.1037/1076-898x.14.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Offside decisions by expert assistant referees in association football: Perception and recall of spatial positions in complex dynamic events.

Abstract: This study investigated the offside decision-making process in association football. The first aim was to capture the specific offside decision-making skills in complex dynamic events. Second, we analyzed the type of errors to investigate the factors leading to incorrect decisions. Fédération Internationale de Football Association (FIFA; n ϭ 29) and Belgian elite (n ϭ 28) assistant referees (ARs) assessed 64 computer-based offside situations. First, an expertise effect was found. The FIFA ARs assessed the tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 54 publications
6
76
1
3
Order By: Relevance
“…A number of previous studies examining the implied motion of simple objects have shown that the forward displacement of an object increases as the object's implied velocity also increases (Finke et al, 1986;Freyd & Finke, 1985; see also Hubbard & Bharucha, 1988, for an example of apparent-motion effects). Similarly, Gilis, Helsen, Catteeuw, and Wagemans (2008) found that the magnitude of the error in offside situations was significantly greater when experienced soccer referees assessed the final location of a moving defender, as compared to when the defender was static. It is possible that the moving video condition created a similar phenomenon in the presnt study, increasing the magnitude of the anticipatory encoding to a point where it became manifest in the results.…”
Section: Discussionmentioning
confidence: 98%
“…A number of previous studies examining the implied motion of simple objects have shown that the forward displacement of an object increases as the object's implied velocity also increases (Finke et al, 1986;Freyd & Finke, 1985; see also Hubbard & Bharucha, 1988, for an example of apparent-motion effects). Similarly, Gilis, Helsen, Catteeuw, and Wagemans (2008) found that the magnitude of the error in offside situations was significantly greater when experienced soccer referees assessed the final location of a moving defender, as compared to when the defender was static. It is possible that the moving video condition created a similar phenomenon in the presnt study, increasing the magnitude of the anticipatory encoding to a point where it became manifest in the results.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to this qualitative difference, recent evidence from driving (Blättler et al, 2010(Blättler et al, , 2012 and basketball activities (Gorman et al, 2012) has shown that experts can perceive states further in the future than can novices (i.e., quantitative difference; see Gilis, Helsen, Catteeuw, & Wagemans, 2008 for an exception). Consistent with these findings, the present study demonstrated that both baseball and control participants exhibited cognitive extrapolation for a moving target, but the baseball group showed a farther subjective vanishing location than did the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that experts in fast ball sports develop their cognitive extrapolation ability to anticipate the future location of a fast-moving object, thus overcoming limitations in the visual system. However, the question of whether cognitive extrapolation for fastmoving objects is modulated by expertise in fast ball sports has not yet been studied [however, see Gilis et al (2008) for similar studies with soccer].…”
Section: Introductionmentioning
confidence: 99%
“…The interrelation of the variables studied in this investigation together with others such as the number, velocity, trajectories and relative positions of the players, distance of the assistant referee to the players (with possible occlusions) and psychological factors underlying the judgments (score, crowd, pressure) are elements that increase the complexity of the scenario. The limitations of the human visual system to process the information in these complex situations is an additional source of incorrect offside judgments (Baldo, Ranvaud, & Morya, 2002;Belda Maruenda, 2004;Gilis, Helsen, Catteeuw, & Wagemans, 2008;Helsen et al, 2006). For instance, on and off the field training sessions that are in line with the physical and perceptual-cognitive demands of the game should be implemented for top-class assistant referees to reduce the number incorrect offside decisions (Catteeuw, Gilis, Wagemans, & Helsen, 2010c;Catteeuw, Gilis, Jaspers, Wagemans, & Helsen, 2010d;Catteeuw, Helsen, Gilis, Van Roie, & Wagemans, 2009b;Gilis, Helsen, Catteeuw, Van Roie & Wagemans, 2009).…”
Section: Discussionmentioning
confidence: 99%